Parâmetros biológicos da cochonilha da raiz Dysmicoccus sp. (Hemiptera: Pseudococcidae) e flutuação populacional em diferentes variedades de mandioca (Manihot esculenta, Crantz) - Zanini, Agostinho (2014)
The cochineal Dysmicoccus sp. has been observed in the culture of the cassava, Manihot esculenta Crantz, in Central Southern Brazil, and there is no information about its biology, population fluctuation, and behavior in this culture. Thus, the aims of this study were to evaluate the biology and population fluctuation of this insect, as well as to evaluate the biological parameters in several cassava cultivars. Both studies were developed at the Laboratory of Biological Control, at the State University of Marechal Cândido Rondon, under controlled conditions. The population fluctuation was developed in the Experimental Field cultivation areas of the Agronomic Institute of Parana (IAPAR). For the studies performed in the laboratory, nymphs not older than one day were inserted into transparent PVC cages and attached to the tuberous roots. The experimental design was completely randomized, obtaining the average of embryonic, nymphal, pre-ovipositional, ovipositional, and longevity stages, according to which the fertility life chart was determined, in which the Cascuda cultivar was used as a substrate. In order to evaluate the cassava cultivars, this process was performed using the Santa Helena, Baianinha, IAC 90, and Cascuda cultivars. The data was submitted to an analysis of variance, and the averages were compared by means of Tukey s test with a probability 5%. To observe the population fluctuation, the samplings were carried from November, 2011 to November, 2013, cultivated with White Starch, Baianinha and Cascuda, each one cultivated in the space of one hectare. The samplings were performed every fifteen days, and 10 plants were collected randomly, in zigzag, and the cochineals quantified. A graphic descriptive analysis was developed based on the average number of nymphs, adults, as well as egg masses, including the precipitation average (mm) and minimum and maximum temperatures (oC). The results indicated that the female presented three nymphal instars, with a duration of 31.1 days, pre-ovipositional period of 21.2 days, and oviposition of 11.6 days, with a fecundity of 219.9 eggs, fertility 97.8%, and embryonic period of 5.4 days. The male presented four instars with a duration of 33.3 days and winged adult stage with a longevity of 3.5 days. The period to complete a generation was of 55.6 days, the net reproduction rate was of 155.3 times and the necessary time for the population to double was of 7.6 days. There was the occurrence in the development of Dysmicoccus sp. when fed with the cultivar IAC 90, showing variations in the Nymphal and pre-oviposition periods, if compared to the others cultivars. It was verified that the precipitation and temperature influenced the population fluctuation of the cochineal, occurring population growth in the period when the precipitations were low and the temperatures remained high